Role of Primary Cilia in Skeletal Disorders - Li, Xinhua; Guo, Song; Su, Yang; Lu, Jiawei; Hang, Donghua; Cao, Shao; Fu, Qiang; Li, Ziqing (Stem Cells International, 2022)
Primary cilia are highly conserved microtubule-based organelles that project from the cell surface into the extracellular environment and play important roles in mechanosensation, mechanotransduction, polarity maintenance, and cell behaviors during organ development and pathological changes. Intraflagellar transport (IFT) proteins are essential for cilium formation and function. The skeletal system consists of bones and connective tissue, including cartilage, tendons, and ligaments, providing support, stability, and movement to the body. Great progress has been achieved in primary cilia and skeletal disorders in recent decades. Increasing evidence suggests that cells with cilium defects in the skeletal system can cause numerous human diseases. Moreover, specific deletion of ciliary proteins in skeletal tissues with different Cre mice resulted in diverse malformations, suggesting that primary cilia are involved in the development of skeletal diseases. In addition, the intact of primary cilium is essential to osteogenic/chondrogenic induction of mesenchymal stem cells, regarded as a promising target for clinical intervention for skeletal disorders. In this review, we summarized the role of primary cilia and ciliary proteins in the pathogenesis of skeletal diseases, including osteoporosis, bone/cartilage tumor, osteoarthritis, intervertebral disc degeneration, spine scoliosis, and other cilium-related skeletal diseases, and highlighted their promising treatment methods, including using mesenchymal stem cells. Our review tries to present evidence for primary cilium as a promising target for clinical intervention for skeletal diseases.